EFEKTIVITAS KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU OLEH DINAS PENDIDIKAN PROVINSI LAMPUNG (Studi Pada SMA Negeri 2 Bandar Lampung) - Megasari, Ayu Selia; Pramazuly, Ayu Nadia; Mosshananza, Hinfa (Universitas Muhammadiyah Lampung, 2023)
ABSTRACTIn Lampung Province, this zoning system has been implemented in every school, one of which has been applied to SMAN 2 Bandar Lampung. The zoning system is a New Student Admission system that is enforced by determining the radius of the student zone domiciled in the nearest zone radius with a certain percentage of the total number of students to be accepted. This study aims to determine the effectiveness of implementation in the Admission of New Students at SMAN 2 Bandar Lampung and in this study used a skinative research method. The results of this study show that the zoning system policies implemented by the Lampung Provincial Education Office, one of which is implemented at SMAN 2 Bandar Lampung have been running quite well and can be said to have run effectively because they are in accordance with the zoning system policy in accepting students with the regulation of the Minister of Education and Culture No. 44 of 2018.Keywords : Effectiveness, Policy, Zoning, Education